Status of Natural Regeneration of Mangroves in Southern Nigeria - Ufuoma Akpovwovwo; Tinuola Ekanade (Journal of Natural Resources and Environmental Management)
Mangroves of the Niger Delta in Nigeria have experienced increased degradation due to years of oil exploration/pollution, urbanization, and population explosion. However, studies on mangroves' natural recovery capacity and juvenile requirements are limited. Therefore, this study examined the relationship between natural mangrove regeneration and sediment parameters in the western Niger Delta. The study was conducted in four locations (Agge, Burutu, Opuama, and Kurutie) and a control location in Ifie. Twenty quadrats of 20 × 20 m were laid at each location. Juvenile species composition and density were obtained from sub-quadrats (10 × 10 m). Sediment samples, totaling 100, were taken from 0 to 30 cm depth within each quadrat. The sediment parameter concentrations were determined using standard laboratory procedures. Mangrove juveniles were classified, based on height, into seedlings (< 40 cm), saplings (40–150 cm), and young trees (1.5–3m), with saplings forming a major proportion. Partial least squares regression was used to evaluate the effects of sediment parameters on mangrove juveniles. Calcium, magnesium, sand, organic carbon, electrical conductivity, total acidity, clay, effective cation exchange capacity, salinity, and bulk density were significant predictors of juvenile mangrove species abundance. A high potential for regeneration, particularly for Rhizophora spp. juveniles, has been established. The establishment of mangrove conservation and reforestation projects is therefore recommended.